Body image among overweight adolescents (teenagers) and their families in Togo - (:unkn) unknown (My University, 2024)
In the West, several studies on the psychopathology of overweight attribute it to being a somatic action expressing or resulting from an individual and/or family psychological malaise of the adolescent. Excess weight which would therefore be a symptom of an unconscious image of the individual and/or family body carrying marked narcissistic fragilities (Carof, 2017; Sanahuja & Vicente, 2018; Benoît 2020). However, our study carried out in an African socio-cultural context tends to demonstrate the opposite and allows us to underline the importance of the socio-cultural crucible of evolution of the overweight adolescent or not, in the construction of his body image. In fact, the Western psychopathological understanding of overweight, like other Western psychopathological theorizations, depends on the socio-cultural environment of identification, emergence and evolution of the phenomenon or problem. An apprehension and psychopathological theorizations of overweight which may therefore not make sense at all in another socio-cultural context. Indeed, overweight in the African socio-cultural framework in general and Togolese in particular is first and foremost a body phenomenon, banal like a small, short, tall, or thin body. Socio-culturally, the overweight body is perceived as signifying a development of body and mind reflecting health and economic well-being. To describe an overweight person in many African countries, they are said to be “in shape”. Thus, overweight is not immediately pathologized or even less psychopathologized in Africa. It only becomes a problem of the body, and again only a medical pathological problem when it is a case of severe, morbid, or massive obesity because it handicaps the subject's daily life and health.It is therefore this phenomenon of the fat, overweight body through its unconscious image of the individual and family body among adolescents in Togo that this present study proposes to explore, discover, describe,
Keywords: African Research